2015
DOI: 10.1007/s00339-015-9394-7
|View full text |Cite
|
Sign up to set email alerts
|

Composition and microstructure of Roman metallic artefacts of Southwestern Iberian Peninsula

Abstract: The Roman invasion introduces new alloys and metallurgical practices in Iberian Peninsula. The southwestern end of this region has many evidences of connections with the Roman World, but there are no studies about the manufacture and use of copper-based artefacts during this period. Therefore, a set of about 20 ornaments, tools and small attachments recovered at the Roman sites of Monte Molião and Cidade das Rosas was studied by an analytical approach combining micro-EDXRF, optical microscopy, SEM-EDS and Vick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
1
3
0
1
Order By: Relevance
“…The values of 5.2 and 6.0% for Sn and 23.2 and 19.0% for Pb, respectively, determined in previously published works on small-sized, decorated castings recovered in Portugal dated to the Roman period, i.e., a patera handle with centaurus [17] and the decorated handle of a jug [19], are similar to the ones of leaded bronze handle attachments from Conimbriga.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…The values of 5.2 and 6.0% for Sn and 23.2 and 19.0% for Pb, respectively, determined in previously published works on small-sized, decorated castings recovered in Portugal dated to the Roman period, i.e., a patera handle with centaurus [17] and the decorated handle of a jug [19], are similar to the ones of leaded bronze handle attachments from Conimbriga.…”
Section: Resultssupporting
confidence: 70%
“…Recently, the analysis of a small set of Roman fibulae and decorated plaques from the archeological site of Castanheiro do Vento (Northern Portugal) determined different types of bronzes alloys -low-and high-tin bronzes, and high-tin leaded bronzes -evidencing technological and economic choices, indicative of the Roman period [18]. A further recent study of different artifacts from Monte Molião and Cidade das Rosas (Southwestern Lusitania province) showed similar variable tin contents (between 2 and 14%) related to the artifacts' function and also high-leaded bronze (19% Pb) used for a decorated handle [19]. Brass and gunmetal alloys were also identified, although only in Cidade das Rosas, a Roman site with a later chronology.…”
Section: Introductionmentioning
confidence: 96%
“…It was postulated that the convenience of recycling broken objects to produce a similar bronze alloy was widely practiced by ancient foundry men. In contrast, Valerio et al 283 reported that the composition of about 20 artefacts from the Roman occupation of the southwestern Iberian Peninsula showed a good correlation with function, based on a multi-technique approach that included m-EDXRF spectrometry. Roman plumbing was the subject of interest of Gomes et al, 284 who used the m-EDXRF and m-Raman techniques to characterise the joint area of thirteen lead water pipes from Conimbriga and Augusta Emerita (Portugal/Spain).…”
Section: Archaeological and Cultural Heritagementioning
confidence: 93%
“…All the prehistoric brass vestiges were small wares with diversi ed categories, scattered throughout various locations. These were found to have nothing in common with copperzinc binary alloys, but contained lead and tin and exhibited uneven structure and large composition segregation, meaning that the raw materials used were cogeneration ores of multiple metals [9,11,47] . The development of Chinese brass smelting technology had experienced three stages: (1) occasional synthesis of brass by doping copper-zinc symbiotic ore during copper smelting; (2) combined smelting of calcite and pure copper; (3) pure copper and elemental zinc smelting.…”
Section: Speculative Reasons For the Use Of Brassmentioning
confidence: 99%